Analisis Kelayakan Investasi Manajemen Aset pada Distribusi Jaringan Listrik dengan Information Economic - Nunuk Wahyuningtyas; Erma Suryani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2016)
PLN as institutions of public service providers, must provide the maximum service to its customers. Electrical power distribution system is part of the main asset continues to develop, it is necessary for improving the quality of good asset management. In this study will be carried out analysis of investment decisions related to asset management by using a dynamic system that makes it possible to study and understand the dynamic behavior of a system, as a means to make investment decisions management. Backed by an investment appraisal method Economic Information this research can provide input to the PLN management in determining the appropriateness of the investment appraisal. Based on the results of the scenario, it should be the replacement of the cable assets of tract homes and substation transformers. Then analyzed by the method of economic information, the final score line cord investment houses and substation transformers at PLN Pamekasan by 38 is included in the category of "Enough" is based on IE Projects Predicate table. It means that the investment is indeed feasible by Management of PLN.